Keberkesanan Penggunaan Mesin Pengorek Terowong (Tunnel Boring Machine) bagi Projek MRT di Malaysia : Perspektif Kontraktor - Mazlan, Nuradilaizzah; Omar, Roshartini; Sarpin, Norliana; Mohamed, Sulzakimin (Research in Management of Technology and Business, 2020)
Tunnel Boring Machine (TBM) is a machine used by contractors to dig tunnels for MRT construction projects in Malaysia. However, the use of TBM machines causes problems of soil structure and soil conditions become unstable and problems in machine proofread. This study was conducted to identify the problems encountered in the use of TBM machines use and to enhance the effectiveness of the use of TBM machines. Qualitative data collection methods in terms of semi-structured interviews were conducted with contractors that using of TBM machines. Data analysis was carried out by project managers and tunnel machine operators including experienced Chinese skilled workers that using TBM machines. The results found that the construction of tunnels using TBM machines has problems with soil structure as well as difficulties in operating the machine. These problems affect the effectiveness of the TBM machine in terms of machine usage capacity, cost, time and quality. The results of the research could provide an insight into the Malaysian construction project organisations and will provide valuable guidelines, in particular to public and private sectors in Malaysia that are looking forward to participating in the global construction market.